PERBEDAAN PERSONAL SOSIAL ANTARA ANAK TK DAN TPA DI PENDIDIKAN ANAK USIA DINI (PAUD) TKIT INSAN HARAPAN KEBONAN, NGAWEN, KLATEN - Linda Ayu Mardiana; Kemaludin .; Ika Widiyanti (STIKES DUTAGAMA KLATEN, 2015)
Background: Personality or behavior (personal social), namely the aspects related to the ability to independently, socialize and interact with the environment, Knowing and understanding child development will create an environment and play while learning process comfortable (favorable), the child can develop optimally. self-care or self-hygiene. Objective: This study aims to find out the difference between Kindergarten Social Personal and Daycare in Early Childhood Education (ECD) TKIT Insan Harapan Kebonan, Ngawen, Klaten. Research methods: Study comperative research with cross sectional approach, the population is taken all children kindergarten and 4-5 years old landfill in Early Childhood Education (ECD) TKIT Insan Harapan Kebonan Ngawen Klaten as many 93 children and semple as many 56, the research instrument using the checklist according to the Denver Development Stress Test (DDST). Research result: From there the characteristics of respondents aged 4-5 years are normal social personal (N) as many as 36 children (64.4%) and 8 children (14.3%) had development of suspect (s) and 1 child (1.8 %) which can not be tested or failed (T) last child in a normal landfill development (N) 11 children (19.6%). Conclusion: There was no significant difference in the Social Personal Kindergarten Children between Daycare in Early Childhood Education (ECD) TKIT Insan Harapan Kebonan Ngawen Klaten, with the result t=-1.553 and p=0.126 (p>0,05) So, Ho will be accept and Ha will be ignore.